Globally incentives-compatible contracts under weak third party enforcement - Raul V. Fabella (University of the Philippines, School of Economics (UPSE), 2005)
We explore how the structure of incentives contracts adjusts to the creation of quasi-rents by the delivery of certain types of contract obligations under weak third party enforcement (TPE). The situation invites quasi-rent appropriation by some contractor. We focus on possible ex-post opportunism by the principal. We propose the concept of globally incentives compatible (GIC) contracts, where no contractor has the incentive to deviate ex-post from the obligations set ex-ante in the contract. We model optimal appropriation by the principal and the response of the agent when the contract is not GIC. The conditions that guarantee GIC for principal-agent the incentives contracts under weak TPE are investigated.
Keywords: 330; global incentives compatibility; quasi-rent; third party enforcement incentives contract; Vertragstheorie; Anreizvertrag; Prinzipal-Agent-Theorie